The Zodiac Series: 10 Erotic Short Stories for Scorpio - Salt, Vanessa (Saga Egmont, 2023)
'The Zodiac 10 Erotic Short Stories for Scorpio' is a collection of erotica that aligns with this sexually dynamic water sign. When fun is on the cards, Scorpios are a very willing partner with intensity and passion. They might not get past the physical relationship but these Scorpio stories are guaranteed to enjoy everything the bedroom has to offer.